Spontaneous pneumomediastinum as a complication in human bocavirus infection. Issue 5 (October 2014) - Pekcan, Sevgi; Gokturk, Bahar; Uygun Kucukapan, Hasibe; Arslan, Ugur; Fındık, Duygu
Abstract The most common causes of spontaneous pneumomediastinum (SPM) in children are asthma attack and respiratory tract infection. Here, we describe a case of SPM in a human bocavirus‐infected 2‐year‐old boy with bronchiolitis.